PENGARUH JOB INSECURITY DAN STRESS KERJA DENGAN LINGKUNGAN KERJA SEBAGAI VARIABEL INTERVENING TERHADAP KINERJA KARYAWAN PADA MASA PANDEMI COVID 19 - Hazimah Hasna’ni; Setiani Setiani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
With an uncertain work environment, and can change considering the Covid19 pandemic has lasted until now, making employees feel confused, worried and afraid and feel insecure while working (Job Insecurity), whether there will be layoffs, salary cuts, opportunities for promotions as well. still uncertain. In addition, employees may also experience work stress, due to the uncertainty of the work environment, workloads that are more than usual, changing work systems, then stress that is influenced by job insecurity felt by employees, resulting in stressed and decreased employee performance which will later lead to a decrease in employee performance. affect the company itself. In this study using quantitative research type of explanatory research, the sample used is all employees of Gets Hotel Malang as many as 50 employees, data collection techniques carried out by researchers are through observation and questionnaires.